Hybrid Gibbsite Nanoplatelet/Cellulose Nanocrystal Multilayered Coatings for Oxygen Barrier Improvement - Chemin, Maud; Heux, Laurent; Guérin, David; Crowther-Alwyn, Laura; Jean, Bruno (Frontiers in Chemistry, 2019)
We have investigated the ability of multilayered hybrid thin films of cellulose nanocrystals (CNCs) and gibbsite nanoplatelets (GNPs) to be built by the layer-by-layer (LbL) technique onto substrates selected for packaging applications, and to improve the oxygen barrier properties. Using complementary structural characterization techniques, namely atomic force microscopy, ellipsometry, and spectral reflectance, we show that when deposited onto model silicon substrates these hybrid films were homogenous and of reduced porosity, and were comprised of alternately deposited monolayers of GNPs and CNCs. The successful deposition of such homogeneous and dense hybrid thin films onto various types of flexible substrates showing different chemical compositions, hydrophilicity, and surface morphology, ranging from cardboard to smart paper, polyethylene (PE) films, and PE-coated cardboard was also confirmed by scanning electron microscopy observations. In view of the diversity of these substrates we could confirm the remarkable robustness of such a deposition process, likely due to (i) the adaptability of the LbL assembling technique and (ii) the strong electrostatic and hydrogen bonding interactions between GNPs and CNCs. The measurement of the oxygen transmission rate (OTR) at 23°C and 50% RH showed that the oxygen barrier properties of the bare substrates could be significantly improved (e.g., 75% decrease of the OTR) after the deposition of such thin (<100 nm) multilayered hybrid films. This lowered permeability was tentatively attributed to the highly tortuous morphology of the coating, acting to impede the gas diffusion. These partially biosourced very thin films stand as good candidates for using as coatings showing high oxygen barrier performance.